BIOLOGY OF THE THREADFIN BREAM, NEMIPTERUS JAPONICUS (BLOCK) - Krishnamoorthi, B (Indian Journal of Fisheries, 2011)
Nemipterus Japonicus attains an average length of 150 mm in the I year; 210 mm at the end of II year; and 240 mm at the end of III year. The fishery along the Andhra- Orissa coast is supported by fish which have completed one year. November marks the commencement of spawning and N. japonicus may spawn for the first time at 160-170 mm and for a second time, perhaps, at 220 mm. N. japonicus is undoubtedly a carnivore, feeds substantially on crustaceans, molluscs, annelids and echinoderms in that order of abundance and in one of the 1,726 stomachs examined over a three year period, vegetable matter was encountered. It is actively predaceous and possibly a sight-feeder. There was a certain degree of regurgitation, particularly during the spawning period from November to March. The feeding intensity did not increase with an increase in size, but the nature of food components was size-dependent. There was a significant increase in the feeding intensity as A’’. japonicus advanced to maturity. The peak catches in the fishery coincided or followed peaks in feeding intensity.